Changes in occlusal plane through orthognathic surgery Alteração do plano oclusal na cirurgia ortognática - Lucas Senhorinho Esteves; Carolina Ávila; Paulo José Medeiros (Dental Press Editora, 2012)
INTRODUCTION: A conventional ortho-surgical treatment, although with good clinical results, does not often achieve the desired functional outcomes. Patients with dentofacial deformities, especially those with increased occlusal planes (OP), are also affected by muscle, joint and breathing functional disorders, as well as facial esthetic involvement. The surgical manipulation of the OP in orthognathic surgery is an alternative to overcome the limitations of conventional treatment. OBJECTIVE: To report the importance of assessing the occlusal plane during diagnosis, planning and ortho-surgical treatment of patients with facial skeletal deformities and its main advantages. CONCLUSION: Although both philosophies of ortho-surgical treatment (conventional and by surgical manipulation of the OP) have presented good results, the selective correction of the OP allows a full treatment of these patients, providing better esthetic and functional results. INTRODUÇÃO: o tratamento ortocirúrgico convencional, embora apresente bons resultados clínicos, muitas vezes não alcança resultados funcionais desejáveis. Os pacientes com deformidades dentofaciais, principalmente os que possuem plano oclusal (PO) aumentado, são acometidos também por distúrbios funcionais musculares, articulares e respiratórios, além do comprometimento estético facial. A manipulação cirúrgica do PO na cirurgia ortognáticaé uma alternativa para suprir as limitações do tratamento convencional. OBJETIVO: relatar a importância da avaliação do plano oclusal nas fases de diagnóstico, planejamento e tratamento ortocirúrgico de pacientes com deformidades esqueléticas faciais, e suas principais vantagens. CONCLUSÃO: apesar de ambas as filosofias de tratamento ortocirúrgico (convencional e pela manipulação cirúrgica do PO) apresentarem bons resultados, a correção seletiva do PO permite um tratamento integral desses pacientes, propiciando melhores resultados estéticos e funcionais.